PERANCANGAN APLIKASI SURVEI JUMLAH PERSENTASE RELAWAN DI SEMUA WILAYAH DAPIL (DAERAH PEMILIHAN) CALON LEGISLATIF PADA PEMILIHAN UMUM: Array (JiTEKH, 2019)
This research is based on recent decades in Indonesia which adopted a general election format to look for Legislative members who would occupy seats in the House of Representatives (DPR) whether in the central, provincial or municipal districts. Each of the Political Parties nominated his cadres to occupy the seat, as well as his cadres who became more and more vigorous to increase their popularity and gain as much sympathy from volunteers as possible. But not a few also the candidates took shortcuts by using money politics in gaining support. Using such politics will have a negative impact on the community as well as the candidate. For the community, it will be a bad example in democracy, while for candidates it will drain a lot of money and make it no longer think of their duties when elected, but he thinks how to return the money he spent to become a legislator and finally corruption. Moreover, if he is not elected, it will greatly affect his life and not a few will go crazy. The above can actually be overcome by using existing technology, namely applying an application that can see the percentage of volunteers who will support it when the election will take place. At least this application can be a benchmark for the candidate to make a decision whether he will run for office or not by seeing the chance he can win or not. If indeed the percentage of volunteers is large then he must be confident to win without having to use money politics. But if indeed the percentage of volunteers is small then he does not need to force himself to use money politics to boost vote acquisition which is sure to be detrimental and not good. In this study the software engineering methodology used in this design is object oriented and the tools used are UML graphic diagrams. While the system design used is web-based.